Integrating multiple “omics” analysis for plant metabolites and their functions - ZHOU Guoyan; HU Wangxiong; XU Jianhong; XUE Qingzhong (浙江大学学报. 农业与生命科学版, 2013)
A comprehensive analysis of a series of metabolites that produced by the organisms in the life processes will help to reveal the biological links between genotype and phenotype. Metabolomics is the method to analyze the metabolites by “omics”, which includes genomics, transcriptomics, and proteomics. To understand the biological response of plants to environmental stimuli or genetic interference, the application of the advanced analytical techniques combined with subsequent generation sequencing and the statistical methods were made for the extraction of information, data interpretation, identification and quantification of cellular metabolites. With the accumulation of high-throughput sequence information, emerged newly metabolomics database can be used not only to store, manage and analyze metabolomics data, but also to provide the chemical structure, physical and chemical properties and pharmacological properties, spectroscopy, experimental process, as well as to interpret the biological function of the metabolites. This paper described briefly several rather special metabolomics database resources (such as KEGG, METLIN, TOMATOMA, ReSpect, ECOMICS, PRIMe). Today, the effect of abiotic stress on plant metabolic spectrum is a focal point of metabolomics research. We reviewed the latest progress on plant responses to multiple environmental stresses such as hypoxia, UV-B radiation, high temperature, strong freezing, light and temperature environment, drought, and lack of sulfur and nitrogen. Future research will be mainly focus on the “key” variable site that decides the single biosynthetic step. This strategy can be used to identify genes and specific ways of crops and medicinal plants. Effects of mutations and transgenic event on plant metabolites have been attracted extensive attention. Glucosinolate (GSL) metabolic pathways provide a useful model system for the research of genome structure of the quantitative characters, while the genome-wide association studies (GWAS) fast become the preferred method for analyzing complex quantitative traits. Transgenic plant overexpressing will lead to the alteration of metabolites and proteins that could help to enhance the multiple stress tolerances. However, the safety assessment of genetically modified crops for food will still be questioned. Instead of relying only on a single analytical technique, identification of the metabolites needs integrating multiple “omics”. In the long-term evolutionary process, the plants will synthesize new metabolites due to the mutation from the metabolic pathways of the plants. The previous study showed genes that encoded the biosynthetic enzymes in plant metabolic pathways were co-regulated through the transcription factors. Thus, the chemical diversity of the plants is closely related to evolution of the transcription factors.